Cognitive-behavioural phenotype in a group of girls from 1.2 to 12 years old with the Incontinentia Pigmenti syndrome: Recommendations for clinical management. Issue 4 (2nd October 2017) - Pizzamiglio, Maria Rosa; Piccardi, Laura; Bianchini, Filippo; Canzano, Loredana; Palermo, Liana; Fusco, Francesca; D'Antuono, Giovanni; Gelmini, Chiara; Garavelli, Livia; Ursini, Matilde Valeria
ABSTRACT: Incontinentia Pigmenti (IP, OMIM#308300) is a rare X-linked genomic disorder (about 1, 400 cases) that affects the neuroectodermal tissue and Central Nervous System (CNS). The objective of this study was to describe the cognitive-behavioural profile in children in order to plan a clinical intervention to improve their quality of life. A total of 14 girls (age range: from 1 year and 2 months to 12 years and 10 months) with IP and the IKBKG/NEMO gene deletion were submitted to a cognitive assessment including intelligence scales, language and visuo-spatial competence tests, learning ability tests, and a behavioural assessment. Five girls had severe to mild intellectual deficiencies and the remaining nine had a normal neurodevelopment. Four girls were of school age and two of these showed no intellectual disability, but had specific disabilities in calculation and arithmetic reasoning. This is the first description of the cognitive-behavioural profile in relation to developmental age. We stress the importance of an early assessment of learning abilities in individuals with IP without intellectual deficiencies to prevent the onset of any such deficit.